Tingkat Penghidupan Berkelanjutan (Sustainable Livelihood) Masyarakat di Desa Kalampadu Kabupaten Ogan Ilir: Analisis Menggunakan SEM-PLS - Yulasteriyani Yulasteriyani; Cynthia Azhara Putri; Istiqoma Istiqoma; Muhammad Yusuf Abror; Diana Dewi Sartika (Society, 2025)
This study examines the relationship between Pentagon Assets (PA), Livelihood Strategies (LS), and Sustainable Livelihood (SL) in the community of Kalampadu Village, Ogan Ilir Regency, using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research framework is based on the Sustainable Livelihood (SL) theory proposed by Scoones (1998) and further developed by DFID (1999). This study adopts an associative research design with a quantitative approach to assess the community's level of sustainable livelihood through statistical analysis. Data were collected through observations, questionnaires, and literature reviews. The sampling method used was probability sampling, with a sample of 188 households selected from a total population of 354, determined using Slovin’s formula. The collected data were analyzed using SEM-PLS. The findings reveal that PA has a significant influence on LS, with a path coefficient of 11.976, while LS makes a substantial contribution to SL, with a path coefficient of 5.136. These results indicate that asset ownership strongly affects livelihood strategies, which in turn supports the achievement of sustainable livelihoods. This study provides valuable insights for policymakers to develop asset-based strategies aimed at enhancing well-being through sustainable livelihood approaches. Policies should emphasize community empowerment, the adoption of green technologies, environmentally friendly skills training, and collaboration among the government, private sector, and local communities to achieve efficient and well-monitored sustainable development.